2021
DOI: 10.1038/s41598-021-97147-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of diffraction and spectroscopic techniques to unveil the crystal structure of antimonic acid

Abstract: The elusive crystal structure of the so-called ‘antimonic acid’ has been investigated by means of robust and state-of-the-art techniques. The synergic results of solid-state magic-angle spinning nuclear magnetic resonance spectroscopy and a combined Rietveld refinement from synchrotron X-ray and neutron powder diffraction data reveal that this compound contains two types of protons, in a pyrochlore-type structure of stoichiometric formula (H3O)1.20(7)H0.77(9)Sb2O6. Some protons belong to heavily delocalized H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…No pre-edge features were observed, and a quite flat post-edge shape was clearly seen. A detailed XAS study on antinomy simple and mixed oxides can be found elsewhere. , The inset of Figure d exhibits the features B k ( k = 1, ..., 5) at ∼6, 16.1, 34.5, 55.7, 92 eV ( E – E 0 ), respectively, B 1 being the white line.…”
Section: Resultsmentioning
confidence: 99%
“…No pre-edge features were observed, and a quite flat post-edge shape was clearly seen. A detailed XAS study on antinomy simple and mixed oxides can be found elsewhere. , The inset of Figure d exhibits the features B k ( k = 1, ..., 5) at ∼6, 16.1, 34.5, 55.7, 92 eV ( E – E 0 ), respectively, B 1 being the white line.…”
Section: Resultsmentioning
confidence: 99%
“…Polyantimonic acid ((H 3 O) 2 Sb 2 O 6 • nH 2 O, denoted as PAA), also denominated as hydrated antimony pentoxide, is known as a proton conductor with high resistance (close to dielectric behavior ~0.5 MΩ), [36,37] has been extensively studied in fields of separation progress, photocatalysts, electrochemistry. [38] It is also capable of forming alloys with lithium [39] with superior lithium adsorption energy and surface diffusion barriers to facilitate lithium nucleate and govern uniform lithium deposition. Noting that Li 3 Sb alloy features low interfacial resistance [40] and faster lithium-ions diffusion (Li + diffusion coefficient is 2×10 À 4 cm 2 s À 1 ) than many other Li-rich alloys, [41] such as LiÀ Ag (10 À 8 cm 2 s À 1 ), [42] LiÀ Mg (10 À 11 cm 2 s À 1 ), [43] and LiÀ Sn (1.9×10 À 7-5.9×10 À 7 cm 2 s À 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyantimonic acid ((H 3 O) 2 Sb 2 O 6 ⋅ n H 2 O, denoted as PAA), also denominated as hydrated antimony pentoxide, is known as a proton conductor with high resistance (close to dielectric behavior ~0.5 MΩ), [36,37] has been extensively studied in fields of separation progress, photocatalysts, electrochemistry [38] . It is also capable of forming alloys with lithium [39] with superior lithium adsorption energy and surface diffusion barriers to facilitate lithium nucleate and govern uniform lithium deposition.…”
Section: Introductionmentioning
confidence: 99%
“…As an important antimonial functional material in industry, polyantimonic acid (PAA, (H 3 O) n H 2– n Sb 2 O 6 ), [ 13 ] possessing a unique interconnected tunnel‐type pyrochlore crystal structure and pentavalent antimony species, could be a low‐cost, high‐capacity anode candidate for LIBs. However, the extremely low intrinsic conductivity of PAA and large volume variation during lithiation reactions lead to severe electrochemical irreversibility and unfavorable cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Among various candidates, antimony-based materials including metallic Sb and Sb oxides, sulfides, selenides, and alloys have attracted much attention because of the fruitful merits of high theoretical capacity, suitable working potential (0.6-0.9 V), wide availability, and eco-friendliness. [11,12] Although each of these reported antimony-based anode materials has claimed unique high-capacity and high-rate performance advantages over graphite, few have yet been identified as a viable and competent alternative, particularly for applications that require both high areal capacity and high volumetric energy density.As an important antimonial functional material in industry, polyantimonic acid (PAA, (H 3 O) n H 2-n Sb 2 O 6 ), [13] possessing a unique interconnected tunnel-type pyrochlore crystal structure and pentavalent antimony species, could be a low-cost, high-capacity anode candidate for LIBs. However, the extremely low intrinsic conductivity of PAA and large volume variation during lithiation reactions lead to severe electrochemical irreversibility and unfavorable cycling stability.…”
mentioning
confidence: 99%